Diskursus Fatwa Cryptocurrency di Indonesia - M. Burhanudin (SIL'AH: Jurnal Ekonomi Syariah, 2025)
This study aims to describe the views of fatwas on cryptocurrency from the Indonesian Ulema Council, Bahsul Masail Nahdhotul Ulama Special Region of Yogyakarta, and East Java. This normative research on Islamic economic law uses a comparative approach. Data was obtained through documentation techniques. The results of the study show that there are diverse views in the fatwas from various institutions regarding the status of cryptocurrency in Indonesia. First, the Bahsul Masail Nahdlatul Ulama Special Region of Yogyakarta institution states that cryptocurrency is permissible in terms of commodities and currency. Second, the Indonesian Ulema Council divides its fatwa decisions, among others, that it is not permissible to use cryptocurrency as a means of payment. Furthermore, trading commodities or digital assets in the form of cryptocurrency is not permissible. Finally, cryptocurrency that meets the requirements as a commodity or asset has a clear basis and provides tangible benefits. Third, the East Java Nahdlatul Ulama Bahsul Masail Institute stated that cryptocurrency is not included in the commodity category. This study confirms that the issue of the legal status of cryptocurrency in Indonesia has given rise to a variety of opinions in Islamic law.